2011
DOI: 10.2320/matertrans.m2010273
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hydrogen Diffusion on the Mechanical Properties of Austenite 316L Steel at Ambient Temperature

Abstract: This study examined how the strain rate affects the room-temperature tensile behavior of hydrogen-charged 316L stainless steels. A hightemperature homogenization treatment was applied to the specimens after hydrogen charging and copper electroplating to remove the hydrogen concentration gradient. A softening phenomenon was observed in the hardening behavior of the H-charged and homogenized specimen at a strain rate of 2 Â 10 À3 /s. The observation was further confirmed by an inspection of the fracture surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(26 citation statements)
references
References 38 publications
2
24
0
Order By: Relevance
“…They found that cathodic hydrogen charging produced major surface hardening. In general, hydrogen charging increases hardness of metallic materials (plain carbon steels, austenitic stainless steels, stainless steels, Ti alloy) [3,[35][36][37], but for some alloys a limited effect on hardness, or even opposite effect: H-induced softening, was observed [38].…”
Section: Ailure Analysis Of Boiler Tubementioning
confidence: 99%
“…They found that cathodic hydrogen charging produced major surface hardening. In general, hydrogen charging increases hardness of metallic materials (plain carbon steels, austenitic stainless steels, stainless steels, Ti alloy) [3,[35][36][37], but for some alloys a limited effect on hardness, or even opposite effect: H-induced softening, was observed [38].…”
Section: Ailure Analysis Of Boiler Tubementioning
confidence: 99%
“…However, the effectiveness of these treatments on methanol mass transfer has not been evaluated. In addition to the initial methanol content in the paper, the mass transfer of the methanol is determined by two key parameters; i.e., the diffusion coefficient (D) and the solid-air partition coefficient (K d ) [9]. Therefore, it is important to determine these coefficients of methanol in the paper materials with different surface treatments in order to accurately assess the risk to human health posed by the use of these paper products in food packaging.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is used also as a standard construction material in engineering applications and nuclear power facilities due to its superior mechanical properties such as high strength, good ductility, high fracture toughness, excellent corrosion resistance and a low rate of absorption for neutron radiation [3,4]. In practice, 316L stainless steel has been studied extensively in order to further improve the thermal and mechanical properties through tailoring of its microstructure and chemical composition [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%